Caring for a child with Attention Deficit Hyperactivity Disorder and disruptions in the parental bond : A qualitative study (Poster) - Yahya, Fatahyah; Sochos, Antigonos (University of Bedfordshire, 2011)
Objectives: Previous research suggests that parents of children with Attention Deficit Hyperactivity Disorder often experience communication problems and conflict in their relationship. The aim was to explore parents' subjective experience and identify main processes by which caring for a child with ADHD may generate distress in the parental relationship. Design: The study was qualitative, interview-based. Methods: Twenty-four parents with a child suffering from ADHD were recruited from relevant charities based in the UK and interviewed for about 45 minutes. A semi-structured interview schedule was used, focused on how parents experienced caring for their child and the potential impact they thought such caring may have had on their couple relationship. All interviews were audio-taped and transcribed. Results: Thematic analysis of the transcripts identified three main themes: Theme 1 referred to the various sources of stress parents felt were put on them directly by the behaviour of their child (e.g. managing aggressive or anti-social behaviour); Theme 2 referred to parents' experience of having too little intimate time with their partners as a result of their child's increased needs; and Theme 3 referred to parental conflict experienced as being caused by their child's needs. Conclusions: Findings may have identified specific interpersonal processes in the couple that are disrupted while caring for a child with ADHD. Parents' inability to devote time to each other may be a central process by which the emotional bond of the couple is disrupted.